How Are Proteins Reduced in the Endoplasmic Reticulum?. Issue 1 (January 2018) - Ellgaard, Lars; Sevier, Carolyn S.; Bulleid, Neil J.
Abstract : The reversal of thiol oxidation in proteins within the endoplasmic reticulum (ER) is crucial for protein folding, degradation, chaperone function, and the ER stress response. Our understanding of this process is generally poor but progress has been made. Enzymes performing the initial reduction of client proteins, as well as the ultimate electron donor in the pathway, have been identified. Most recently, a role for the cytosol in ER protein reduction has been revealed. Nevertheless, how reducing equivalents are transferred from the cytosol to the ER lumen remains an open question. We review here why proteins are reduced in the ER, discuss recent data on catalysis of steps in the pathway, and consider the implications for redox homeostasis within the early secretory pathway. Trends: Correct disulfide formation within the secretory pathway requires both disulfide bond formation and disulfide reduction. Protein thiol modification is reversed by protein disulfide isomerase (PDI) family members localized to the ER. A pathway links thioredoxin reduction in the cytosol to disulfide reduction in the ER. Misfolded ER proteins need to be reduced before targeting for destruction in the cytosol. The unfolded protein response (UPR) transducers Ire1 and ATF6 are regulated by disulfide bond formation and reduction. The key regulator of protein folding and the UPR, BiP, is modulated by reduction catalyzed by the non-canonical oxidoreductase Sil1.